Unsteady MHD Casson Fluid Flow through Infinite Inclined Plate in the Presences of Hall Current and Chemical Reaction - Husna Izzati, Osman; Zulkhibri, Ismail; Ling, Dennis Chuan Ching; Nur Fatihah, Mod Omar; Vieru, Dumitru (Semarak Ilmu Publishing, 2023)
The objective of this paper is to study about the unsteady Casson fluid in the present of hall current and chemical reaction electrically conducting heat fluid near an infinite inclined plate. Casson fluid model is choose to be in this research to characterize the non-Newtonian fluid behaviour. The exact solutions of momentum, energy and concentration equations, under Boussinesq approximation were obtained by Laplace transform technique to transform governing partial diffrential equations into ordinary differential equations with an appropriate boundary condition. All the transformed equations are then solved numerically by using Mathematica. Finally, the exact solution of momentum, energy and concentration of the cases are gained. The results of flow features for different values of governing parameters, unsteadiness parameter and Casson parameter are evaluated in graphs and has been discussed in the results section. The result presented that the velocity is increase when the magnetic parameter increases due to the existence of Lorentz force that helps in reducing heat for electronic system and radiators. Furthermore, the Hall current that we added into this study makes the velocity increase when Hall current increase. These phenomena happened because of the rising of Hall current makes the conductivity become decrease which led the decreasing in magnetic damping, results the increase in velocity.